Physical and catalytic properties of high silica faujasites - Stanbridge, Nicholas Henry John (1995)
The research described in this thesis was conducted over a total of three years during the period October 1990 to October 1994, and is the sole work of the author, unless indicated otherwise by reference. A series of mildly dealuminated Y zeolites has been prepared by hydrothermal treatment using a low partial pressure of water vapour. These materials, together with samples previously dealuminated under more severe conditions, were characterised by the temperature programmed desorption of ammonia and the catalytic activity for suitable test reactions. Advances in technique permitted simultaneous monitoring of both the deammoniation and dehydroxylation processes. Interesting features were observed in the dehydroxylation traces which were related to changes in the acid site strength and amount of extraframework aluminium. The activity for both n-hexane cracking and toluene disproportionation reaches a maximum, corresponding to a framework concentration of 25-30 structural aluminium atoms per unit cell, consistent with the maximum number of strong acid sites. Slight deviation from this behaviour was noted, with the mildly steamed catalysts having lower activities than would be expected on the basis of their framework compositions alone. An in-depth analysis of the cracking of n-hexane has revealed that the extent of reaction is also critically dependent on the density of the available acid sites, which is explained in terms of the reaction mechanism. The disproportionation of toluene has highlighted differences in the nature of the extrastructural aluminium. The catalytic activity of the materials is either decreased or enhanced on extraction depending on whether the catalysts have been prepared by mild or severe dealumination. Variations in product distribution with time on stream have been observed and accounted for by changes in the reaction. The lifetime and activity profile of the catalyst could be altered by exposure of the catalyst to small amounts of toluene prior to the main reaction. This supports the concept of active coke enhancing this reaction. Cumene dealkylation was found to proceed on weaker acid sites than the cracking of n-hexane and the disproportionation of toluene, although a maximum in activity was still observed. This indicates that the weakest sites are not capable of catalysing this reaction, and that some heterogeneity of site strength exists between strong and weak acid sites. The dehydration of propan-2-01 was confirmed as a reaction which assesses the total number of acid sites, regardless of strength. However, changes in the selectivity of the products with the strength of the acid sites were found, implying that the formation of di-isopropylether is favoured by strong sites. Deliberate coking of the catalyst surface by exposure to propan-2-01 at elevated temperatures was found to increase the measured activity, in addition to changing the selectivity almost entirely in favour of propene. Extraframework aluminium was found to play an important role in all of the reactions studied. This emphasises the view that although structural aluminium has the larger influence on the overall activity of a catalyst for a particular reaction, the nature of the extraframework aluminium cannot be overlooked.